Motivasi Belajar, Media Pembelajaran, Kemampuan Membaca Terhadap Hasil Belajar IPS - Urfiyati (Jurnal Penelitian dan Pendidikan IPS, 2019)
This study aims to: 1. analyze the effect of learning motivation, learning media, and the ability to read books on learning 2. Learning motivation on learning outcomes. 3. Learning media on learning outcomes. 4. The ability to read books on learning outcomes. Quantitative study is used in this research which the population of class XI IPS SMAN 1 GALIS PAMEKASAN students, sampling techniques using a total sampling of 90 respondents. Research Instrument is an independent variable questionnaire and value of the results of daily tests to be bound. Data analysis techniques consist of multiple regression analysis, classic assumption tests and hypothesis testing. Hypothesis testing results show: 1). There is a significant influence of learning motivation, learning media and the ability to read books together on learning outcomes that is 99.8%. 2). There is a significant influence on learning motivation, on learning outcomes. 3). There is a significant influence of learning media on learning outcomes. There is a significant influence of the ability to read books on learning outcomes. Teachers should be able to increase enthusiasm and arouse student learning with the presence of learning motivation, learning media and the ability of available books.